Organizational, legal, and technological dimensions of information system administration - Portela, Irene Maria, 1965-; Almeida, Fernando, 1979-; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Ave., Hershey, PA, 17033) : IGI Global, 2014)
'This book recognizes the importance of information technology by addressing the most crucial issues, challenges, opportunities, and solutions related to the role and responsibility of an information system, highlighting various aspects of the organizational and legal implications of system administration'--Provided by publisher.
The role and responsibilities of the system's administrator / Filipe Moreira, Joel Luz -- Trust management and delegation for the administration of web services / Michele Tomaiuolo -- Academic and professional qualifications of the systems administrator required to work in the organizational context / JosMonteiro, Mio Lous{u4860}-- Beyond compliance: understanding the legal aspects of information system administration / Peter J. Wasilko -- Due diligence in cyberspace / Joanna Kulesza -- Criminal liability of organizations, corporations, legal persons, and similar entities on law of Portuguese cybercrime / Gon{u386C}o S. de Melo Bandeira -- Redressing violations of privacy: the case of Portuguese'e-invoice' / Irene Marie Portela -- Role of cloud systems as enabler of global competitive advantages / Fawzy Soliman -- Cloud computing: IT governance, legal, and public policy aspects / Carlos Juiz, Victor Alexander de Pous -- Information security and information assurance: discussion about the meaning, scope, and goals / Yulia Cherdantseva, Jeremy Hilton -- A conceptual framework for big data analysis / Fernando Almeida, Mio Santos -- The role of security culture / Jo Malcolmson -- The 2011 survey of information security and information assurance professionals: findings / Yulia Cherdantseva, Jeremy Hilton -- Mitigation of security concerns of VoIP in the corporate environment / Fernando Almeida, JosCruz -- Practical approach for data breach cases in ERP systems / Pedro Sousa, JosCosta, Vitor Manso.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 09/19/2013).
Keywords: Management information systems; Computer networks -- Management; Computer security; Computer security -- Law and legislation; Big data analysis; Cloud computing; Cybercrime; Information security policy; IT policy and standardization; Management science; Network security